Contribution to the stratigraphy of the non-marine Tertiary deposits on the south coast of the Nûgssuaq peninsula northwest Greenland with remarks on the fossil flora - Koch, B. Eske (Meddelelser om Grønland, 1959)
The Tertiary, sedimentary sequence on the south coast of the Nûgssuaq peninsula, North Greenland (THE UPPER ATANIKERDLUK FORMATION) is described. The type area on the south-eastern part of the peninsula (the Atanikerdluk area) shows the Upper Atanikerdluk formation divided into 5 members: Plateau basalts Point 976 member Aussivik member Umiussat member Naujat member Quikavsak member Cretaceous (Atane formation) The Plateau basalts rest upon the Upper Atanikerdluk formation which again rests unconformably upon the Atane formation (Cretaceous). The first occurrence of subaeric lavas is found in Aussivik member. West of the type area (Pautût and more westerly) the basalt volcanism began earlier, and here the number of sedimentary members of the type area substituted by products of the volcanism (basalt breccia and Plateau basalts) is increasing the more westerly one comes. The basal Quikavsak member is only visible locally owing to its origin as an infilling of a river-valley in connection with the Paleocene transgression. This fossil river-valley can be traced from Atanikerdluk (purely fluviatile) by Pautût to Nûk kitdleq, where a marine intercalation has yielded a minor fossil fauna making the Paleocene age probable by its accordance with an occurrence of marine, fixed Lower Paleocene fauna in a delta deposit at Angmârtussut (the Agatdalen valley), whose stratigraphic equivalence to Quikavsak member is proved. With 1) this fixed point in the Agatdalen valley, 2) the faunal agreement between this occurrence and Nûk kitdleq, 3) the agreement between the fossil flora of the fixed occurrence at Angmârtussut and Quikavsak member at Atanikerdluk and the other occurrences of this member at the south coast of the Nûgssuaq peninsula as well as 4) the same position in the geological course of events, all these occurrences of Quikavsak member and the litho-stratigraphically equivalent occurrences at Angmârtussut are linked together as Lower Paleocene deposits. This dating thus applies to the known fossil floras "Upper Atanikerdluk A" and "Upper Atanikerdluk B" of 0. Heer. A short survey of the fossil floras from the localities described is given. Finally Macclintockia Kanei (Hr.) Sew. & Conw. is stated zone fossil of the Lower Paleocene of West Greenland.